Creatine supplementation and multiple sprint running performance - Glaister, M.; Lockey, R. A.; Abraham, C. S.; Staerck, A.; Goodwin, J. E.; McInnes, G. (The Journal of Strength and Conditioning Research, 2006)
The aim of this study was to examine the effects of short-term creatine monohydrate supplementation on multiple sprint running performance. Using a double-blind research design, 42 physically active men completed a series of 3 indoor multiple sprint running trials (15 × 30 m repeated at 35-second intervals). After the first 2 trials (familiarization and baseline), subjects were matched for fatigue score before being randomly assigned to 5 days of either creatine (4·d-1 × 5 g creatine monohydrate + 1 g maltodextrin) or placebo (4·d-1 × 6 g maltodextrin) supplementation. Sprint times were recorded via twin-beam photocells, and earlobe blood samples were drawn to evaluate posttest lactate concentrations. Relative to placebo, creatine supplementation resulted in a 0.7 kg increase in body mass (95% likely range: 0.02 to 1.3 kg) and a 0.4% reduction in body fat (95% likely range: -0.2 to 0.9%). There were no significant (p > 0.05) between-group differences in multiple sprint measures of fastest time, mean time, fatigue, or posttest blood lactate concentration. Despite widespread use as an ergogenic aid in sport, the results of this study suggest that creatine monohydrate supplementation conveys no benefit to multiple sprint running performance.